Edukasi Pemberian Makanan Tinggi Serat Sebagai Camilan Sehat Untuk Pencegahan Obesitas di SMP Negeri 04 Samarinda - Iskandar Muda; Alika Zahra Putri Chandra; Alya Rizah Malihah; Arlyta Gracia Budiman; Christie Karla; Fathiyah Salsabila Azzahrah; Fiona Ika Dewanty; Melly Sabila; Muhammad Idam Alfaroji; Nadila Sawaliya; Tito Ali Hanif; Umi Rahayu; Zanetha (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2025)
Background: Degenerative diseases are chronic conditions that significantly impact an individual’s quality of life and productivity. One example of a degenerative disease is obesity. An imbalance between dietary intake and nutritional needs, along with a sedentary lifestyle, are major contributing factors to the development of many degenerative disorders. Obesity prevention can begin by raising public awareness from an early age about adopting healthier lifestyles. One effective preventive measure is consuming fiber-rich foods. Purpose: The aim of this activity was to provide education about offering high-fiber foods as healthy snacks to help prevent obesity. Method: This activity was conducted on May 15, 2025, at SMP Negeri 4 Samarinda. The educational session included delivering material on high-fiber food as a healthy snacking option for obesity prevention. Evaluation was carried out by comparing the pre-test and post-test results to assess the increase in students' understanding after the session. Results: There were 30 participants. Students' understanding improved after the education session, as indicated by an increase in knowledge levels from 60% in the pre-test to 83.3% in the post-test. Conclusion: There was an increase in knowledge regarding the consumption of high-fiber foods as healthy snacks for the prevention of obesity.